Analisis Kelayakan Panjang dan Tebal Perkerasan Runway Untuk Pesawat Jenis B737-900ER yang Beroperasi di Bandar Udara Banyuwangi - Ariawan, I Putu; Wahyudi, Iqbal; Jayantari, Made Widya (Jurnal Ilmiah Telsinas, 2021)
Runway is an airport facility which is very important for aircraft landing and taking off. The runway is a square area on the surface of the airport that is prepared for aircraft take off and landing, without a well-planned and managed runway, the aircraft will not be able to use the airport. In designing the runway, it is strictly regulated regarding the length, width, orientation (direction), configuration, slope / slope, and thickness of the runway pavement. This final project will analyze the feasibility of the runway length and the thickness of the pavement (runway) for the operational plan aircraft that will be used in the next 20 years. With ARFL corrections to the existing runway conditions, the current runway length is 2,500 meters. For the next 20 years traffic flow is forecasted using linear regression analysis from 2011 to 2037. From the forecasting results, it was found that the total aircraft movement was 19,138 movements (R1), so it was planned to use the B 737 900 ER aircraft because this aircraft had a passenger capacity of 220 seats. This aircraft is the reference for the planning of the runway dimensions. Some of the resulting planning analyzes include: the length of the planned runway is 2,498 meters long and 45 meters wide. Meanwhile, the pavement planning analysis resulted in a surface layer thickness of 4 inches, a base coarse layer of 13 inches, and a subbase thickness of 22 inches.